System Innovation on Purpose - Leadbeater, Charles; Winhall, Jennie (The Rockwool Foundation, 2021)
In Building Better Systems, we introduced four keys to unlock system i nnovation: purpose and power, relationships and resource flows. These four keys make up a set. Systems are often hard to change because powe r, relationships, and resource flows are locked together in a reinforc ing pattern to serve the system’s current purpose. Systems start to ch ange fundamentally when this pattern is disrupted and opened up. Then a new configuration can emerge, serving a new purpose. In this essay s eries we delve deeper into these four keys and provide practical advic e on how they can be put to use. This essay is about the role that pur pose plays in orchestrating complex systems and how system innovators can create a new system around a new sense of purpose.